Predictors of career adaptability skill among higher education students in Nigeria - Amos Shaibu Ebenehi; Abdullah Mat Rashid; Ab Rahim Bakar (International Journal for Research in Vocational Education and Training (IJRVET), 2016)
This paper examined predictors of career adaptability skill among higher education students in Nigeria. A sample of 603 higher education students randomly selected from six colleges of education in Nigeria participated in this study. A set of self-reported questionnaire was used for data collection, and multiple linear regression analysis was used to analyze the data. Results indicated that 33.3% of career adaptability skill was explained by the model. Four out of the five predictor variables significantly predicted career adaptability skill among higher education students in Nigeria. Among the four predictors, career self-efficacy sources was the most statistically significant predictor of career adaptability skill among higher education students in Nigeria, followed by personal goal orientation, career future concern, and perceived social support respectively. Vocational identity did not statistically predict career adaptability skill among higher education students in Nigeria. The study suggested that similar study should be replicated in other parts of the world in view of the importance of career adaptability skill to the smooth transition of graduates from school to the labor market. The study concluded by requesting stakeholders of higher institutions in Nigeria to provide career exploration database for the students, and encourage career intervention program in order to enhance career adaptability skill among the students.
Keywords: 330; VET; Vocational Education and Training; Career adaptability skill; Higher education; Nigeria; Predictors; Students